Effects of Local Stabilizers (Achi, Ofor, And Cocoyam) on the Physicochemical, Sensory and Microbiological Properties of Yoghurt (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This study was conducted to evaluate the use of local soup thickeners known as plant-based stabilizer to produce yoghurt and determine their effects on the physicochemical and microbiological properties of yoghurt. Reconstituted powdered cow milk was homogenized, pasteurized at 95°C for 5 min, cooled to 45˚C and inoculated with a direct-vat-set (DVS) yoghurt starter culture of Streptococcus thermophilus and Lactobacillus bulgaricus for 12 h and cooled at 5˚C. Achi and Ofor seeds were sorted, cleaned, soaked (6 h), toasted, dehulled, dehydrated, milled and sieved to obtain their respective flours. Cocoyam were sorted, peeled, washed, sliced, dehydrated, milled, and sieved to obtain cocoyam flour. These flours were incorporated at 10% into yoghurt samples as stabilizers. The yoghurt samples were subjected to proximate, functional and microbial, and organoleptic evaluation. Proximate analysis revealed significant differences (p
Keywords: Soup thickeners; Plant-based stabilizers; Yoghurt; Yoghurt formulation